'An avalanche of tragedy': Modern girls and the murder of Mrs Mick. (January 2013) - Glasbeek, Amanda
On 24 May 1925, three young women incarcerated at the Concord Industrial Jail Farm for Women (near Toronto, Ontario) wrestled the night matron, Mrs Mick, to the ground, tied her down, took her keys and escaped from prison. Tragically, Mrs Mick suffered a stroke and died while chained to the prison washbasins. Upon their capture, the two 16-year-olds and one 19-year-old were charged with murder in a case that would capture the attention of the local press and hold it for weeks. This article analyses this case as an exemplary instance of the distinctly gendered world of criminal offending. Characterized as 'an avalanche of tragedy' by the local press, the death of Mrs Mick offers historical testimony to the complexity of women's entanglements with the criminal justice system and to the relationship between women's violence and their victimization as criminalized subjects.